تعليم المحادثة باستخدام كتاب "العربية بين يديك" في المرحلة الأولى قسم تعليم اللغة العربية جامعة بنجكولو الإسلامية الحكومية - Ikke Wulandari; Amir Abdullah (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2020)
This research focuses how to teach muhadatsah in the Arabic language section using the Arabiah Baina Yadaik, What are the results of teaching conversation in the Arabic language section using the Arabiah Baina Yadaik? As for the objectives of the research To describe the results of conversation teaching in the Arabic language section using the Arabiah Baina Yadaik? This research is of the qualitative research type in the case study and data is obtained by means of the interview, observation and documents. The researcher chose a data analysis method is a Miles and Huberman analysis, which says about data classification, data presentation, and data summary / conclusion. As for the search results Are learning muhadatsah in the first stage, Department of Teaching Arabic Language, Islamic State University of Bengkulu with listening and speaking skills, then reading and writing skills. As for listening and speaking, the teacher provides dialogue and vocabulary. As for reading and writing skills, the teacher provides grammatical or morphological rules and understanding dialogue. This research was conducted at level 1 Arabic language study program totaling 3 classes. Each class consists of 19 students. Final results muhadatsah scores are taken from the value of the assignment, midterm and final semester exams. For A class, the Muhadatsah score of the " Very Good " category, 5 students were presented to be 26%, and the "good" category, 10 students were presented to be 53% and the "enough" category, 4 people were presented to 21%. Then in B class, the grade of muhadatsah in the category of "Very Good" there were 11 students who were presented to be 58%, the category of "Good" there were 4 people who were presented to be 21% and in the category of "good enough" there were 4 people who were presented to be 21%. And C class, the grade Muhadatsah score of the "Very Good" category there were 6 students presented to 32%, the category of "Good" there were 9 people were presented to be 47% and the category of "Enough" there were 4 people were presented to be 21%.